POLA INTERAKSI SOSIAL MASYARAKAT TRANSMIGRAN BATAK DENGAN MASYARAKAT LOKAL DI NAGARI SUNGAI KUYUNG KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - ELENDITA, ERENDA - (Pendidikan Sosiologi, 2014)
The Nagari Sungai Kuyung Sub Pancung Soal, South Coastal District, there are two tribes that Minangkabau tribe as the locals and the Batak tribes are migrants or migrants. Although different ethnic groups, but human beings can create good social relationships in the community. This study aimed to describe the pattern of social interaction with the local Batak migrants in Nagari Sungai Kuyung South Coastal District. By looking at the elements of social interaction is cooperation, competition and conflict. The theory used in this study is based on the theory of symbolic interactionism of George Herbert Mead. Mead claims that the language allows us to be self-conscious beings (self-couscious), are aware of our individualistic, and a key element in this process is a symbol. The results showed that the patterns of social interaction among the Minangkabau Batak society are: (1). Cooperation: (a). Cooperation In The Field, (b). When cleaning gutters cooperation, (c). Collaboration On Repair Mosque (d), the Partnership Opens New Road, (2). Competition, (a). Competition in the rating and Roles, (b). Competition Tenure, (c). Competition in the market. (3). conflict